Iśakazāde - Trivedi, Amit 1979- (Yash Raj Films, 2012)
Where love and hate collide, this love story is born. Two people who're raised hating each other, break the unwritten family dictate; and fall in love. These outlaws of love thus start a new war
DVD; NTSC all regions ; Dolby digital 5.1; 16:9 widescreen. - Some versions include audio CD soundtrack
Arjun Kapoor, Parineeti Chopra, Gauhar Khan
Director of photography, Hemant Chaturvedi ; editor, Aarti Bajaj ; music, Amit Trivedi ; choreography, Rekha Prakash, Chinni Prakash ; lyrics, Kausar Munir, Habib Faisal
Bonus features : Optional audio feature commentary -- Deleted scenes -- 'Making of' featurette -- LInks to individual songs -- Original theatrical trailer and promos
Keywords: Man-woman relationships